REVOLUSI MENTAL ALA NABI KHIDIR TERHADAP NABI MUSA: Telaah Qur’an Surah Al-Kahfi Ayat 60-82 - Syamsu Syauqani (UIN Mataram, 2019)
Indonesia is currently being hit by a multi-dimensional crisis ranging from economic, moral, to a crisis of self-confidence. Indonesia filters that can fortify its people and even become a soft field for the spread of moral viruses, including drugs, pornography, and value-free media. So President Joko Widodo sparked a term of the mental revolution in 2014. Mental revolution as a movement of change is concerned with the mind, attitude, and character that occurs in humans. This mental revolution aims to change human attitudes and character. Therefore, the perfection of this Qur'anic guidance becomes a reference to be used as a solution in every dynamic of human problems including mental revolution. In this research, the story of the Prophet Khidir and Musa was one of the models in applying the mental revolution.